Lipids in Photosynthesis Essential and Regulatory Functions - Wada, Hajime; Murata, Norio; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
This book provides an essential summary of an exciting decade of research on relationships between lipids and photosynthesis. This book, designed both for scientists whose work focuses on photosynthesis and lipids and for graduate students who are developing an interest in the field, brings together extensively cross-referenced and peer-reviewed chapters by 52 prominent researchers, from 9 countries. The topics covered include the structure, molecular organization and biosynthesis of fatty acids, glycerolipids and non-glycerolipids in plants, mosses, lichens, algae, and cyanobacteria, as well as in chloroplasts and mitochondria. Several chapters deal with the manipulation of the extent of unsaturation of fatty acids and the effects of such manipulation on photosynthesis and responses to various forms of stress. The final chapters focus on lipid trafficking, signaling and advanced analytical techniques. Ten years ago, Paul André Siegenthaler and Norio Murata had edited "Lipids in Photosynthesis: Structure, Function and Genetics," which has been a unique and an authoritative book in the field. The current new volume belongs, beside its predecessor, on every plant and microbiological researcher's bookcase.
Lipids in Thylakoid Membranes and Photosynthetic Cells -- Fatty Acid Biosynthesis in Plants Metabolic Pathways, Structure and Organization -- Biosynthesis and Function of Chloroplast Lipids -- Lipids in Plant Mitochondria -- Plant Sphingolipids: Structure, Synthesis and Function -- Lipids in Algae, Lichens and Mosses -- Molecular Genetics of Lipid Metabolism in the Model Green Alga Chlamydomonas reinhardtii -- Lipid Biosynthesis and its Regulation in Cyanobacteria -- Heterocyst Envelope Glycolipids -- Lipids in the Structure of Photosystem I, Photosystem II and the Cytochrome b 6 f Complex -- The Role of Phosphatidylglycerol in Photosynthesis -- The Role of Glycolipids in Photosynthesis -- Role of Lipids in the Dynamics of Thylakoid Membranes -- Architecture of Thylakoid Membrane Networks -- Regulatory Role of Membrane Fluidity in Gene Expression -- Lipid Trafficking in Plant Photosynthetic Cells -- Regulatory Roles in Photosynthesis of Unsaturated Fatty Acids in Membrane Lipids -- Oxidation of Membrane Lipids and Functions of Oxylipins -- Biosynthesis and Biotechnology of Seed Lipids Including Sterols, Carotenoids and Tocochromanols -- Advanced Mass Spectrometry Methods for Analysis of Lipids from Photosynthetic Organisms.
Keywords: Life sciences; Biochemistry; Lipids; Cell membranes; Botany; Plant physiology; Life Sciences; Plant Sciences; Lipidology; Plant Biochemistry; Plant Physiology; Membrane Biology